Skull Walls: The Peruvian Dead and the Remains of Entanglement. Issue 3 (29th November 2022) - Heaney, Christopher
Abstract: From 1820 through 1920, American anthropologists acquired more human remains of Andean origin than those of any other individual population worldwide. Samuel George Morton, the Smithsonian, Harvard's Peabody Museum of Archaeology and Ethnology, and the American Museum of Natural History all made "ancient Peruvians" core to their collections, racializing the Americas' past and present by using "ancient Peruvians" as a historic set against which living Native Americans might be compared. This process fueled the collection of Indigenous remains in general and confirms Americanist historians' need to attend to entanglement: US scholars were adapting a Peruvian tradition of knowledge and grave robbing in which the Andes possessed the Americas' oldest, wealthiest, most "civilized, " and most plentiful human remains. It also reminds us that recent and useful conceptualizations of early American history as vast had disturbing early republican counterparts—in this case, a violent science that entangled precolonial, colonial, and republican North and South American temporalities and embodied them in the "historic" Indigenous dead. Reckoning with history's role in colonization includes recognizing the literal, even spirited, remains of entanglement as historical forces in their own right, with temporalities beyond those of the United States.